2016
DOI: 10.1371/journal.pone.0163665
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Horizontal DNA Gene Transfer by Extracellular Vesicles

Abstract: The biological relevance of extracellular vesicles (EV) in intercellular communication has been well established. Thus far, proteins and RNA were described as main cargo. Here, we show that EV released from human bone marrow derived mesenchymal stromal cells (BM-hMSC) also carry high-molecular DNA in addition. Extensive EV characterization revealed this DNA mainly associated with the outer EV membrane and to a smaller degree also inside the EV. Our EV purification protocol secured that DNA is not derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 50 publications
6
95
0
Order By: Relevance
“…The horizontal DNA gene transfer by exosomes released from BMSC was identified. It carries high‐molecular DNA, which was mainly associated with the outer exosome membrane for the exchange of genetic information mediating the intercellular communication during cell evolution and development 30 . In addition, exosomes were able to package and transfer their mitochondrial DNA to breast cancer cells, leading to restoration of metabolic activity and increased self‐renewal potential 27 …”
Section: Introductionmentioning
confidence: 99%
“…The horizontal DNA gene transfer by exosomes released from BMSC was identified. It carries high‐molecular DNA, which was mainly associated with the outer exosome membrane for the exchange of genetic information mediating the intercellular communication during cell evolution and development 30 . In addition, exosomes were able to package and transfer their mitochondrial DNA to breast cancer cells, leading to restoration of metabolic activity and increased self‐renewal potential 27 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of DNA packaging in EV are poorly understood and whether DNA is packaged within the membrane‐bound space of EV remains unclear. Recent studies have revealed that DNA is not contained within the membrane‐enclosed space of EV, but is largely attached to the outer surface of EV . Indeed, treatment of EV with nucleases such as DNase I and Exonuclease III before DNA extraction significantly reduces the overall DNA detected from cancer cell‐derived EV (Yumi Kawamura and Takahiro Ochiya, 2017, personal observation), demonstrating that DNA is mainly associated with the outer EV membrane (Fig.…”
Section: Do Ev Contain Dna?mentioning
confidence: 99%
“…Since the discovery of extracellular DNA, it has been suggested that cancer cells may deliver oncogenic sequences via EVs, which might result in the transformation of surrounding normal cell types akin to an infection-like process (Bergsmedh et al, 2001;Fischer et al, 2016;García-Olmo et al, 2010;Kanada et al, 2015;Rak and Guha, 2012). Indeed, it has been demonstrated that EVs can impart transformed phenotypes into recipient cell types (characterized by cellular capacity for formation of foci in culture or anchorage-independent growth) (Antonyak et al, 2011;Hallal et al, 2019;Lee et al, 2014;Oushy et al, 2018).…”
Section: Dna Cargomentioning
confidence: 99%